Porosity and permeability properties of Nano black rice hush ash in porous concrete pavement - Mohd Rosli, Hainin; Mohd Ibrahim, M. Y.; Mohd Khairul Idham, Mohd Satar; Nordiana, Mashros; Putra Jaya, Ramadhansyah; Mohamad Idris, Ali; M. H., Wan Ibrahim; M. N., Fadzli (IOP Publishing, 2019)
Porous concrete is a concrete with continuous voids, which are purposely incorporated into concrete. The ability of the porous concrete pavement to allow water to percolate into the underlying strata depends on its porosity and permeability, which is one of its most important pore structure features. In this study, porous concrete pavement containing Nano from black rice hush ash (BRHA) was examined through the porosity and permeability test. A 66 nanometres size was used. Results showed that the porosity value of the specimens increases with increasing Nano BRHA content. In addition, the coefficient permeability of specimens was found to increase with Nano BRHA content increased. The results also indicated that the permeability coefficient has a strong correlation with porosity value.